2019
DOI: 10.1167/tvst.8.2.2
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Low-Cost, Wide-Field, Infant Retinal Camera, “Neo”: Technical and Safety Report for the Use on Premature Infants

Abstract: Purpose To report the technical aspects, systemic, and ocular safety of a novel, low-cost, wide-field, infant retinal camera for use on premature infants. Methods The device, the “3nethra Neo” (Neo) is a 120° portable, contact, wide-field, unibody camera, with a CMOS sensor (2040 × 2040 resolution) and a warm light-emitting diode (LED) illumination source. The Neo was used to image 140 awake, preterm infants between postmenstrual age (PMA) of 28 to 37 weeks, undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…A scope for improvement in the existing strategy would be: 1) a universal screening program[28] built on the tenets of tele-medicine employing low cost, easy to use, portable infant imaging cameras,[29] an accredited training program that employs a cadre of trained technicians and an integrated reading center that will provide credible and rapid diagnosis with reports for these remote screening sites which comply with clinical and medico-legal regulations. [30] This has the scope of preventing blind-person years (BPY) accounting for over 200 million USD annually in ten states of the country[31]2) Software innovations providing fully or semi-automated analysis of retinal images providing a clinical triage, machine learning, deep learning algorithms and artificial intelligence will allow better utilization of the limited number of specialists.…”
Section: Unique Problems Require Unique Solutionsmentioning
confidence: 99%
“…A scope for improvement in the existing strategy would be: 1) a universal screening program[28] built on the tenets of tele-medicine employing low cost, easy to use, portable infant imaging cameras,[29] an accredited training program that employs a cadre of trained technicians and an integrated reading center that will provide credible and rapid diagnosis with reports for these remote screening sites which comply with clinical and medico-legal regulations. [30] This has the scope of preventing blind-person years (BPY) accounting for over 200 million USD annually in ten states of the country[31]2) Software innovations providing fully or semi-automated analysis of retinal images providing a clinical triage, machine learning, deep learning algorithms and artificial intelligence will allow better utilization of the limited number of specialists.…”
Section: Unique Problems Require Unique Solutionsmentioning
confidence: 99%
“…This observation is further supported by the enhanced ratio of mRNA levels of Bax/Bcl2. We as well as others have a shown that the ratio of Bax/Bcl2 determines the cell susceptibility to apoptosis 71 74 . However, in the presence of SAHA, the MMC induced apoptosis of cells were prevented.…”
Section: Discussionmentioning
confidence: 63%
“…The fluorescent images were documented using ProgRes Capture Pro 2.5 software on fluorescent microscope (Olympus BX41). Fluorescence intensity was quantified using Image J 1.48 version software ( http://imagej.nih.gov/ij/ ; provided in the public domain by the National Institutes of Health, Bethesda, MD, USA) 74 . Primary and secondary antibodies are listed in Table 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Whether to document retinopathy of prematurity (ROP) or retinoblastoma or retinal hemorrhages, a contact fundus camera, such as the RetCam, RetCam Shuttle (Natus USA, formerly Clarity, MSI, USA), or 3nethra Neo,[ 1 ] (Forus Health, Bengaluru, India) makes it easier to get a clearly focused retinal photograph. It reduces movement of the eyeball and the camera as compared to a non-contact method.…”
Section: Ease Of Usementioning
confidence: 99%